Variation in nodulation and N2 fixation by the Gliricidia sepium/Rhizobium spp. symbiosis in a calcareous soil - Sanginga, N.; Manrique, K.; Hardarson, G. (1991)
Variation in nodulation and N2 fixation by the Gliricidia sepium/Rhizobium spp. symbiosis was studied in two greenhouse experiments. The first included 25 provenances of G. sepium inoculated with a mixture of three strains of Rhizobium spp. N2 fixation was measured using the 15N isotope dilution method 12 weeks after planting. On average, G. sepium derived 45070 of its total N from atmospheric N2. Significant differences in fixation were observed between provenances. The percentage of N derived from atmospheric N2 ranged from 26 to 68070 (equivalent to 18-62mg N plant-I) and was correlated with total N in the plant (r = 0.70; P = 0.05). The second experiment included six strains of Rhizobium spp. and two methods of inoculation and the plants were harvested 14,35 and 53 weeks after planting. In the first harvest significant differences were found between the number of nodules and the percentage and amount of N2 fixed. There was also a significant correlation between the number of nodules and the amount of N2 fixed (r = 0.92; P = 0.05). In the final harvest no correlation was observed, although there were significant differences between the number of nodules and the percentage of N derived from the atmosphere. The amount of N2 fixed increased with time (from an average of 27070 at the first harvest to 58070 at the final harvest) and was influenced by the Rhizobium spp. strain and the method of inoculation. It ranged from 36070 for Rhizobium sp. Strain SP 14 to 71070 for Rhizobium SP 44 at the last harvest. Values for the percentage of atmosphere derived N2 obtained by soil inoculation were slightly higher than those obtained by seed inoculation.